Evaluating Primary Care Providers' Compliance with Special Capitation in Indonesia's National Health Insurance - Anindita, Rahma; Aryani, Ari Dwi; Ritonga, Rahmad Asri; Darmasurya, Aditya; Trisnanto, Tedo Arya; Tsani, Pranatawati Nur; Yudanto, Bayu; Trisnasari, Trisnasari (Jurnal Jaminan Kesehatan Nasional, 2024)
To increase the effectiveness of the special capitation payment scheme implemented by the primary care providers (PCPs), to expand health service coverage and to provide additional incentives for the health workforce in remote areas, a commitment agreement with the primary care provider has been established. However, the PCP's achievement after implementing the commitment agreement was unclear. Hence, this study aims to analyse the commitment and achievements of the PCP in the special capitation payment scheme in 2021 and 2022. About 178 PCPs in 2021 and 191 PCPs in 2022 across Indonesia were included in this descriptive analysis using the quantitative method. The results reflected that special capitation payments accompanied by commitment agreements might influence increasing the capacity, access, and quality of health services. There was a 58% increase in the number of PCPs that achieved all PCP commitment indicators for capitation recipients in 2022 compared to 2021. The highest commitment indicator attained by PCP recipients of special capitation is the sending of health personnel. The quantity of capitation rates received, the simplicity of using capitation funds, the accessibility of physicians and other health professionals, and the assessment of service commitment accomplishments, which will affect payment, all influence the achievement of commitment indicators.